OPTIMALISASI PEMANFAATAN DAUN PANDAN UNTUK DIJADIKAN KAP LAMPU YANG BERNILAI EKONOMIS TINGGI DAN RAMAH LINGKUNGAN GUNA MENDUKUNG SUSTAINABLE DEVELOPMENT GOALS - Ahmad Samikh (Universitas Muria Kudus, 2021)
Pandanus plants that grow and spread widely in Indonesia, so attention is needed to optimize their use so that they are not considered pests. Optimization activities have benefits for the preservation of the surrounding environment. The activity of optimizing pandanus leaves is created by making plaits that have a higher selling value and are environmentally friendly, namely products made from pandanus lampshades. The SWOT analysis method is carried out in this activity. The results achieved in this activity were that there was an increase in the use of pandanus leaves and income from business owners and stakeholders.